Analysis of Fabric Raw Material Inventory Control in Backpack Products Using the Material Requirements Planning (MRP) Method at CV. Metassa Collection - Wiwik Sudarwati; Andreas Tri Panudju (PT FORMOSA CENDEKIA GLOBAL, 2023)
Inventory of raw materials is an important factor in the company so that the supply of raw materials in CV. Metassa Collection must be sufficient to guarantee the needs for the smooth running of production activities. The purpose of this study is to determine the supply of raw materials with the Material Requirements Planning method. The method used is Material Requirement Planning (MRP). In calculating the MRP, the methods used are Lot For Lot and Economic Order Quantity (EOQ). The results of the research on the smallest forecasting calculation using the Linear Regression method with MAD values ​​of 274.52, MSE 114.536, and MADE Based on MRP calculations with the Lot Sizing EOQ method produce a total cost of Rp. 2,811,032,000. The minimum ordering of raw materials using the EOQ method for controlling raw material inventory at CV. Metassa Collection.